PENETAPAN ALTERNATIF PELAKSANAAN PROYEK BERDASARKAN KRITERIA BIAYA PADA PEMBANGUNAN SARANA DAN PRASARANA KOMPLEK ISLAMIC CENTER DI SAMPIT - Ratri, Ika Wahyuninng (Universitas 17 Agustus 1945 Surabaya, 2014)
For contractors, profit is one of the goals in an project activities. Therefore, planning the implementation of activities by considering the concept of time value of money in financial analysis is very important and very useful to keep the cash flow that will be generated in order for project to succeed as a expected. This study aims to assess the feasibility of an investment decision and predict future profits are adjusted to the prevailing bank interest aplly within the time frame specified net present valueÂ method.Â The result of this study indicate that the value of the maximum profit that can be generated from the optimization of the cost and time that has been implemented exclude taxs is forÂ 26.87 % or Rp. 15.158.527.000,- (fifteen billion worth of one hundred fifty-eight million five hundred twenty seven thousand rupiah)Key words : time value of money, net present value, project management.